2018
DOI: 10.1016/j.toxlet.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and potential multigenerational epigenetic effects linked to uranium chronic low-dose exposure in gonads of males and females rats

Abstract: Altogether, our work demonstrates for the first time a sex-dependance and inheritance of epigenetic marks, DNA methylation, as a biological response to the exposure to low doses of uranium. However, it is not clear which type of reproductive cell type is more responsive in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
13
2
Order By: Relevance
“…The mRNA and protein expression levels of the DNMT3A gene in cancerous testicular tissues were significantly higher than those of the DNMT3A gene in normal testicular tissues (Chen et al 2014). Chronic low-dose exposure to uranium increased the global methylation level in the rat testes as well as the mRNA expression levels of the DNA methyltransferase genes DNMT1 and DNMT3A/B; this DNA methylation profile was maintained across generations (Elmhiri et al 2018). Here, both mRNA and protein expression levels of the three DNA methyltransferases (DNMT1, DNMT3A, and DNMT3B) were significantly lower in the TP testicular tissues than those in the YP testicular tissues.…”
Section: Discussionmentioning
confidence: 91%
“…The mRNA and protein expression levels of the DNMT3A gene in cancerous testicular tissues were significantly higher than those of the DNMT3A gene in normal testicular tissues (Chen et al 2014). Chronic low-dose exposure to uranium increased the global methylation level in the rat testes as well as the mRNA expression levels of the DNA methyltransferase genes DNMT1 and DNMT3A/B; this DNA methylation profile was maintained across generations (Elmhiri et al 2018). Here, both mRNA and protein expression levels of the three DNA methyltransferases (DNMT1, DNMT3A, and DNMT3B) were significantly lower in the TP testicular tissues than those in the YP testicular tissues.…”
Section: Discussionmentioning
confidence: 91%
“…For example, exposure to low doses of uranium causes hypermethylation in testis and hypomethylation in ovaries with significant changes in the expression of DNA methyltransferase genes DNMT1 and DNMT3A/B [36]. The effects are maintained across F0, F1, and F2 generations [36]. The sensitivity of DNA methylation changes with age has also been reported: global DNA hypermethylation was found to be associated with high serum levels of persistent organic pollutants in an elderly population [37].…”
Section: Epigenetic Regulation Via Dna Methylationmentioning
confidence: 94%
“…It was suggested that exposure to toxic compounds causes changes in DNA methylation patterns. For example, exposure to low doses of uranium causes hypermethylation in testis and hypomethylation in ovaries with significant changes in the expression of DNA methyltransferase genes DNMT1 and DNMT3A/B [36]. The effects are maintained across F0, F1, and F2 generations [36].…”
Section: Epigenetic Regulation Via Dna Methylationmentioning
confidence: 99%
“…Considerations for how epigenetic effects from environmental exposures may contribute to increased rates of disease presentations in AI populations have not been investigated to date. This is despite the increasing and ongoing research in animal models demonstrating the potential for multigenerational epigenetic health effects from low-dose uranium exposure (Elmhiri et al 2018;Legendre et al 2019). With developing technologies in the field of epigenetics, future research in this area could elucidate transgenerational risk factors that have yet to be formally identified in humans.…”
Section: American Indian Considerationsmentioning
confidence: 99%